Poverty and uncertainty attitudes - Victor H. Gonzalez Jimenez (Tinbergen Institute, 2024)
This paper demonstrates that well-established biases in decision making under uncertainty can generate poverty traps. A theoretical framework is developed to demonstrate that: i) probability weighting and ambiguity attitude can lead individuals to erroneously undervalue profitable investments, and ii) poverty increases the magnitude of these investment errors. The model predicts that poverty is perpetuated by inducing poor individuals to underinvest in profitable opportunities to a greater extent than rich individuals. We empirically validate these theoretical predictions using data from two experiments conducted on a representative sample of American households.
Keywords: O12; D81; D09; I3; 330; Poverty traps; Probability Weighting; Ambiguity Attitude